2020
DOI: 10.1111/bjd.19346
|View full text |Cite
|
Sign up to set email alerts
|

A 10‐year review of surgical management of dermatofibrosarcoma protuberans*

Abstract: Summary Background Dermatofibrosarcoma protuberans (DFSP) is a rare skin cancer. Standard treatment in the UK is either wide local excision (WLE) or Mohs micrographic surgery (MMS). It is unclear which approach has the lower recurrence rate. Objectives We undertook a retrospective comparative review of surgical management of DFSP in the UK National Health Service in order to define (i) current surgical practice for primary and recurrent DFSP, (ii) local recurrence rates for primary DFSP and (iii) survival outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
42
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 25 publications
(57 reference statements)
0
42
1
Order By: Relevance
“…Almost 20% of standard excisions were incomplete at the first attempt. Recurrence rates in the current study were lower than previously reported (1.2% vs. 7%) 1,4 . However, this is probably an underestimation as the median follow‐up time of treated DFSPs in this study was very short (2.2 years).…”
contrasting
confidence: 78%
See 3 more Smart Citations
“…Almost 20% of standard excisions were incomplete at the first attempt. Recurrence rates in the current study were lower than previously reported (1.2% vs. 7%) 1,4 . However, this is probably an underestimation as the median follow‐up time of treated DFSPs in this study was very short (2.2 years).…”
contrasting
confidence: 78%
“…Recurrence rates in the current study were lower than previously reported (1.2% vs. 7%). 1,4 However, this is probably an underestimation as the median follow-up time of treated DFSPs in this study was very short (2.2 years). The Dutch study showed that half of all recurrences occurred after 2 years.…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…Durack et al 16 performed a retrospective comparative review of the surgical management of DFSP in the United Kingdom National Health Service in order to define the local recurrence rate for primary tumors and survival outcomes for DFSP. 483 primary and 64 recurrent DFSP was included; 75% of primary tumors were treated with WLE and 20.1% with MMS.…”
Section: Resultsmentioning
confidence: 99%